2018
DOI: 10.1177/2397847318812794
|View full text |Cite
|
Sign up to set email alerts
|

Aluminium phosphide-induced testicular toxicity through oxidative stress in Wistar rats: Ameliorative role of hesperidin

Abstract: The present study was designed to investigate aluminium phosphide (ALP)-induced testicular toxicity, including its effects on sperm parameters and histological alterations in Wistar rats, and the possible protective role of hesperidin (HSD). Oral administration of ALP at 1.15 mg/kg body weight (1/10 LD50) for 30 days resulted in a significant increase in testicular malondialdehyde, lipid hydroperoxides, and oxidized protein levels. These indicators of oxidative stress were accompanied by decreased activity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 74 publications
3
26
0
Order By: Relevance
“…It is suggested that ROS has a higher affinity for the thiol groups in the biomolecules, leading to the depletion of thiols intracellularly; consequently resulting in reduced GSH concentrations (Irvine, ). Mohamed and El‐Moneim () and Afolabi, Wusu, Ugbaja, & Fatoki () showed in their study, Al administration reduced the activity level of antioxidant enzymes. In our study, AlCl 3 administration led to an increase in MDA levels, decreased levels of GSH and diminished CAT activity.…”
Section: Discussionmentioning
confidence: 91%
“…It is suggested that ROS has a higher affinity for the thiol groups in the biomolecules, leading to the depletion of thiols intracellularly; consequently resulting in reduced GSH concentrations (Irvine, ). Mohamed and El‐Moneim () and Afolabi, Wusu, Ugbaja, & Fatoki () showed in their study, Al administration reduced the activity level of antioxidant enzymes. In our study, AlCl 3 administration led to an increase in MDA levels, decreased levels of GSH and diminished CAT activity.…”
Section: Discussionmentioning
confidence: 91%
“…The unsaturated fatty acids undergo oxidation which is detrimental to sperm cell, germ cell membrane, eventually inducing cell death (Proudfoot, 2007). Excess ROS can also damage biomolecules (DNA, lipids and proteins) thus, altering the morphology and functions of the testes (Uzunhisarcikli et al, 2007;Afolabi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The observed decrease in both SOD and CAT activities indicated a breakdown of enzymatic system due to Zn-P-induced oxidative stress. A reduction in SOD activity usually leads to an increased level of superoxide anion, which can subsequently inactivate CAT activity [31]. Conversely the inability of CAT to prevent H 2 O 2 accumulation in the cell could lead to inactivation of SOD.…”
Section: Discussionmentioning
confidence: 99%